Nigeria’s agrifood system: Structure and drivers of transformation - Andam, Kwaw S.; Diao, Xinshen; Ecker, Olivier; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2024)
Nigeria’s agrifood system (AFS) diagnostic results Nigeria’s AFS lacked transformation between 2009 and 2019 • Primary agriculture is larger than off-farm AFS and its share in total GDP did not fall • Off-farm share of AgDP+ barely changed over time AFS growth has been mainly driven by domestic-market-oriented value chains • Less-traded value chains dominated the AFS both in terms their size and contribution to AFS GDP growth • Domestic consumption patterns (and changing diets) are therefore important drivers of agricultural transformation Looking forward, the structure of AFS growth will be crucial in driving development outcomes… (e.g., poverty, dietary improvements, employment creation, and growth) Jointly promoting these value chains would offer an effective way to achieve multiple development outcomes